Neoadjuvant therapy in pancreatic ductal adenocarcinoma: A competing risk analysis. Issue 3 (27th May 2022) - Pacilio, Carlo Alberto; Grassi, Elisa; Gardini, Andrea; Fappiano, Francesca; Passardi, Alessandro; Frassineti, Giovanni Luca; Tamberi, Stefano; Ercolani, Giorgio
Abstract: Objective: Most patients with pancreatic ductal adenocarcinoma receive chemo‐radiotherapy as first approach, some of them with the future hope to undergo surgery. Methodology: The aim of the study was to estimate the probabilities to receive surgery, to experience tumour progression or post‐operative recurrence. We performed a competing‐risk approach to estimate competing events of disease progression and surgery, as well as post‐operative recurrence and death without recurrence. Results: Of 96 enrolled patients, 49 received chemotherapy because they were judged borderline resectable, 21 were locally advanced and 7 had liver‐only limited metastatic disease. Competing‐risk analyses showed that resectability status at diagnosis not only determines future probabilities of surgery, but also tumour progression and post‐operative recurrence ( p < .05 in all cases). CA19‐9 decrease ≥50% predicted surgery ( p = .032), whereas CA19‐9 ≥ 300 U/mL predicted post‐operative recurrence ( p = .001). Younger age also predicted surgery ( p = .001) and margin status predicted recurrence ( p = .047). The combination of the competing events suggested that the best outcomes since diagnosis depended not only on resectability and final surgical margin, but also on the combination of relative decrease of CA19‐9 and its absolute value after therapy. Conclusions: The combination of CA19‐9 decrease, added to resectability criteria, can be used to optimise the selection of surgical candidates.